Bioprocess-inspired synthesis of multilayered chitosan/CaCO3 composites with nacre-like structures and high mechanical properties. Issue 28 (2nd July 2021) - Li, Yidi; Ping, Hang; Zou, Zhaoyong; Xie, Jingjing; Wang, Weimin; Wang, Kun; Fu, Zhengyi
Abstract : Nacre-like chitosan/CaCO3 composites were fabricated by a microscale additive manufacturing mineralization method at room temperature. The synthetic composites show excellent underwater superoleophobicity and exhibit mechanical properties. Abstract : The formation of natural structures found in biological systems is wonderful and can be completed at ambient temperatures in contrast to artificial technologies wherein harsh conditions are common prerequisites. A new research direction, "bioprocess inspired manufacturing", is proposed for fabricating advanced materials with novel structures and functions. Nacre consists of an ordered multilayer structure of crystalline calcium carbonate lamellae separated by organic layers exhibiting mechanical toughness, which transcends that of its constituent components. Inspired by the nacre formation process, a microscale additive manufacturing mineralization method is proposed for achieving a multilayered organic–inorganic layered structure. In this work, layered calcite was synthesized on the surface of chitosan (CS) films at room temperature under the coordinated control of magnesium ions (Mg 2+ ) and polyacrylic acid (PAA). The CS films and layered calcite are sequentially assembled in a layer-by-layer deposition approach to form an organic–inorganic hybrid structure. The nacre-like chitosan/CaCO3 (CS/CaCO3 ) composites exhibit high transparency and underwater superoleophobicity. Impressively, the hardness (2.35 ± 0.03 GPa) and Young's modulus (58.1 ± 0.5 GPa) of the as-prepared (CS/CaCO3 ) composites are comparable to those of their biological counterparts. This study provides a rational bioprocess-inspired room-temperature mineralization method to develop advanced composite materials with good performance.